2019
DOI: 10.1111/1365-2664.13470
|View full text |Cite
|
Sign up to set email alerts
|

Road verges support pollinators in agricultural landscapes, but are diminished by heavy traffic and summer cutting

Abstract: Supporting pollinators in agricultural landscapes is important for reversing their global decline. Road verges and hedges are used by pollinators for feeding and reproduction, but few studies consider entire pollinator communities, and it remains unclear how they are distributed across adjacent verges, hedges and fields, or how they are affected by traffic and verge cutting. We surveyed flowers and pollinators, using transect counts and pan traps, to explore the role of road verges and their associated hedges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 42 publications
(62 reference statements)
3
68
0
1
Order By: Relevance
“…On the other hand, modern road verges appear to still be in the colonisation and establishment phase and have the potential to develop and gain further species in the future (Isbell et al., 2019; Spooner & Smallbone, 2009). How many species could be gained is likely to depend on other factors such as road verge width, structure and road traffic intensity (Angold, 1997; Jimenez et al., 2013; Phillips et al., 2019), factors which can also covary with road age. Further study across a gradient of different road ages would give a greater indication of the rate build‐up (or gradual loss) of species and specialists over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, modern road verges appear to still be in the colonisation and establishment phase and have the potential to develop and gain further species in the future (Isbell et al., 2019; Spooner & Smallbone, 2009). How many species could be gained is likely to depend on other factors such as road verge width, structure and road traffic intensity (Angold, 1997; Jimenez et al., 2013; Phillips et al., 2019), factors which can also covary with road age. Further study across a gradient of different road ages would give a greater indication of the rate build‐up (or gradual loss) of species and specialists over time.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, as much road verge habitat as possible should be managed for biodiversity, but if practitioners want to identify the most species‐rich verges then we recommend the use of historical maps to find those stretches of roads that are older than 100 years. Although a discussion of appropriate management strategies is beyond the scope of this study, verge cutting at the appropriate time to benefit both plants and pollinators, plus hay removal is likely to have the most positive effect on biodiversity (Jakobsson et al., 2018; Phillips et al., 2019). Due to the apparent long time lags in community assembly, seed sowing can be an option to increase roadside diversity (Auestad et al., 2016), even for road verges that were established several decades ago.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insect abundance was even higher on non-highway road verges than away from roads. Similarly, a recent study showed that road verges and their associated hedges can provide hotspots of resource for pollinators in agricultural landscapes, but their capacity to do so is reduced by heavy traffic (like on highways) [23]. The aim of the present paper was to complement the previous work on insects published by Villemey et al [22], focusing this time on vertebrates (mammals, birds, amphibians and reptiles).…”
Section: Topic Identification and Stakeholder Inputmentioning
confidence: 78%
“…Road verges are often important early or mid-successional habitats providing feeding and reproductive opportunities for pollinators including diverse floral resources (e.g. Halbritter et al, 2015;Noordijk et al, 2009;Phillips et al, 2019) and larval hostplants (e.g. Munguira and Thomas, 1992;Valtonen et al, 2006b).…”
Section: Q1) What Pollinator Communities and Associated Resources Arementioning
confidence: 99%